A study on the socio-economic roles of Waqf ahli (Family waqf) in promoting family security and a sustainable family economy = Kajian mengenai peranan sosio-ekonomi waqf ahli (waqf keluarga) dalam meningkatkan jaminan keluarga dan kemampanan ekonomi keluarga - Mohamad, Nor Asiah (International Islamic University Malaysia, 2018)
The challenges associated with financial stability and sustainability of family economy in the future are increasing. The most worrying is the problems facing the survivors after the death of their breadwinners. The majority of Muslims are rarely ready for this possibility and many lacks the knowledge on how to face such a situation. Some wrongly hold to the view that such preparation is not encouraged in Islam, against the principle of faraidh (estate planning) and an act of avoiding taxation and etc. In this article, it is shown that although waqf (Islamic endowment) appears in the form of charity but the outcomes are tremendous, encompassing family future investment and income generating. Employing a doctrinal analysis by looking into the available literatures on waqf, this article discusses how waqf ahli can contribute to family security and ensure a sustainable family economy. It is shown that Islamic endowment (waqf) aims to preserve and protect property for the use of the public; including spending on family. In addition, family waqf saves the heirs' property or business from fragmentation. Most importantly, it ensures sustainable family financial planning within the Shari‘ah framework while adding value to the existing family property or business.